Research of a Green Hospital Evaluation Index System based on Analytic Hierarchy Process - Xin Xia, Yunlong Ma, Ye Luo, Jianwei Lu (Forest Chemicals Review, 1970)
With an increasing trend of the number of hospital buildings in China, hospital buildings are facing an urgent problem with a lot of demands for energy, and high quality requirements. Focusing on the problem, China has issued the evaluation of green hospital buildings, which provides more accurate quantitative evaluating indicators. According to the recent researches and concepts of green hospital at home and abroad, in order to solve the present problems better in the estimation of green hospital, the lack of an effective evaluation index system for guiding the construction and evaluation of effects in green hospital estimation should be focused on as the main issue. In the investigation of some hospitals on the basis of the expertise consultation, analytic hierarchy process (AHP) is employed to confirm the weight of grade Level-1 and Level-2 indexes of green hospital estimation, and calculate the weights of the combination coefficients for the construction of a green hospital evaluation index system in green healthcare. This paper takes Shanghai East Hospital as a research case, and based on AHP, a set of actual measurement indicators are figured out for evaluating the assessment of the hospital buildings. The evaluation indexes system of green hospital is established with the approach of AHP. Finally, 4 Level-1 indicators, 30 Level-2 indicators and the corresponding index weight coefficients are finally determined. And through the selection of the related evaluation indicators, we can positively make progress for the evaluation systems in green hospital estimation, which will provide useful reference for decision-making of hospital management.